Management of Discharge Planning Implementation on Chronic Renal Failure Patients - Rahayu Winarti; Dwi Retnaningsih; Priharyanti Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2021)
Patients with Chronic Renal Failure experience an inability of the body to remove metabolic waste. Hemodialysis and regulation of nutritional intake are efforts to maintain their health condition. The information provided so that patients understand and comply with the therapy is very important to prevent emergency conditions. Therefore, Discharge Planning is very important on patients with Chronic Renal Failure to provide information concerning the sustainable health needs after patients’ discharge, implementing evaluation and directing the self-care. This study aimed to determine the management of Discharge Planning implementation for clients with chronic renal failure in the Hemodialysis Room at Ungaran General Hospital. The research design used was a case study with an embedded single case study. Participants in the study were nurses and patients with Chronic Renal Failure who were selected using purposive sampling. The data were collected through semi-structured interviews and discharge planning documentation studies. The number of participants in the study were three nurse executors of hemodialysis and 3 patients who received hemodialysis therapy. Informant consent was submitted for the informants' approval prior to the interview. The data collected from the interviews were analyzed using pattern matching techniques. Based on the research, it shows that the role of nurses in the hemodialysis room is the most important in implementing Discharge Planning as educator executor, and managerial role is carried out by the head of the ward.